Breast‐related stereotype threat contributes to a symptom cluster in women with breast cancer. Issue 9 (19th February 2017) - Li, Jie; Gao, Wei; Yu, Li‐Xiang; Zhu, Song‐Ying; Cao, Feng‐Lin
Abstract : Aims and objectives: To investigate the prevalence of breast‐related stereotype threat and its effects on a symptom cluster consisting of anxiety, depression and fatigue and on each symptom. Background: The stereotype that breasts are a sign of women's femininity results in patients with breast cancer fearing diminished femininity and rejection, which may induce psychological problems that co‐occur as a symptom cluster. Design: Cross‐sectional study. Methods: A total of 131 patients with breast cancer postmastectomy completed the study. A question measuring breast‐related stereotype threat, the Hospital Anxiety and Depression Scale and the Functional Assessment of Chronic Illness Therapy‐Fatigue Scale were used to assess their breast‐related stereotype threat and symptoms of anxiety, depression and fatigue. Results: Of the 131 patients who answered the breast‐related stereotype threat question, 86 (65·6%) reported breast‐related stereotype threat. They did not differ significantly in social and clinical characteristics compared with those without the stereotype, but did report significantly higher levels of the symptom cluster and each symptom (anxiety, depression and fatigue). The odds ratios of the stereotype were significant for the symptom cluster, depression and fatigue (odds ratios = 2·52–3·98, p  <   0·05). Conclusion: The breast‐related stereotype threat was common in patients with breast cancer. There was about a twofold increase in their risk of experiencing the symptom cluster and symptoms of depression and fatigue. Relevance to clinical practice: In clinical practice, breast‐related stereotype threat should be measured together with prevalent symptoms (e.g. anxiety, depression and fatigue) in patients with breast cancer. Our findings will aid the development of interventions for improving the mental health of women with breast cancer.